Smart Board Chat System / David Gan Chye Ong - David Gan, Chye Ong (2002)
People need to connect with other people and business processes to get their work done. Much like the step between the telegraph to the telephone, the step to Internet technology connects people with a richer flow of information. Collaboration can bring people all over the world together with more efficient use of time and at lower cost, by eliminating the need to travel. The emergence and wide-spread adoption of the World Wide Web (WWW) offers a great deal of potential for the developers of collaborative technologies, both as an enabling infrastructure and a platform for integration with existing end-user environments. This paper describes a system, which attempts to exploit that potential by extending the WWW to provide a set of basic facilities for collaborative information sharing. The SmartBoard system was conceived as an alternative tools which supports collaborative working for widely-dispersed working groups. This project focuses on building chat tool and whiteboard for collaborative computing. We report on the design and implementation of our system, the requirements of the system and the benefits accruing from our choice of the development tools and using our experiences suggest how recent developments in the WWW point the way to more suitable and powerful mechanisms to support the development of collaborative systems.